Investigation of energy-efficient solid desiccant system for wheat drying - Hanif, Shazia; Sultan, Muhammad; Miyazaki, Takahiko; Koyama, Shigeru (International Journal of Agricultural and Biological Engineering, 2019)
The study investigates the applicability of solid desiccant system for drying of freshly harvested wheat grains in order to reduce the moisture content to an optimum level. Fast and low-temperature drying systems are required by today’s drying industries in order to provide economical and safe drying. Therefore, comparison of desiccant drying has been made with the conventional method in terms of drying kinetics, allowable time for safe storage, the total time for drying cycle, and overall energy consumption. It has been found that the air conditions of proposed desiccant drying system provides a high drying rate and longer allowable storage time for safe drying. As the desiccants possess water adsorbing ability by means of vapor pressure deficit, therefore, the desiccant system successfully provides low-temperature drying which ensures the quality of wheat grains. Overall energy consumption is estimated for both conventional hot air drying and desiccant drying system. It has been found that the desiccant system requires less energy as drying is accomplished at minimum level of air flow and within allowable storage time. In addition, the overall performance index of the desiccant system is higher at all temperatures. The study is useful for developing a low-cost and sustainable drying technology for various agricultural products. Keywords: desiccant, solid desiccant system, drying, grain, wheat, performance evaluation DOI: 10.25165/j.ijabe.20191201.3854 Citation: Hanif S, Sultan M, Miyazaki T, Koyama S. Investigation of energy-efficient solid desiccant system for wheat drying. Int J Agric & Biol Eng, 2019; 12(1): 221–228.